Leadership case studies in education - Northouse, Peter Guy; Lee, Marie (SAGE, 2016)
A look "at leadership through the eyes of educators. The text examines how the major theories and models of leadership apply to education. [...] Peter G. Northouse, Marie Lee, and contributors from all levels of the education discipline provide readers with real-world case studies that illustrate the complex leadership challenges and issues facing educators today"--Back cover.